2017
DOI: 10.3389/fimmu.2017.00870
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Killing of Murine Pluripotent Stem Cells by Natural Killer (NK) Cells Requires Activation by Cytokines and Partly Depends on the Activating NK Receptor NKG2D

Abstract: Natural killer (NK) cells play an important role as cytotoxic effector cells, which scan the organism for infected or tumorigenic cells. Conflicting data have been published whether NK cells can also kill allogeneic or even autologous pluripotent stem cells (PSCs) and which receptors are involved. A clarification of this question is relevant since an activity of NK cells against PSCs could reduce the risk of teratoma growth after transplantation of PSC-derived grafts. Therefore, the hypothesis has been tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
2
9
2
Order By: Relevance
“…Here, we provide evidences that hiPSCs are the target of NK cells in vitro and in humanized mice. In opposition to what was found using murine iPSCs, human NK cells could prevent the formation of teratomas without prior activation [5]. Other than the species differences, such disparity may be explained by the use of a different injection site in our study (renal capsule versus subcutaneous) and perhaps by the high expression level of NK activating ligands (i.e.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Here, we provide evidences that hiPSCs are the target of NK cells in vitro and in humanized mice. In opposition to what was found using murine iPSCs, human NK cells could prevent the formation of teratomas without prior activation [5]. Other than the species differences, such disparity may be explained by the use of a different injection site in our study (renal capsule versus subcutaneous) and perhaps by the high expression level of NK activating ligands (i.e.…”
Section: Discussioncontrasting
confidence: 69%
“…However, the need for pluripotent stem cells to evade immune responses may be required for the growth of teratomas in vivo . Pioneer work by Dressel and colleagues showed that mouse iPSCs can occasionally give rise to teratomas in autologous/syngeneic mice in absence of the activation of the host natural killer (NK) cells [4; 5]. Likewise, human iPSCs were shown to be the target of human NK cells in vitro [6; 7].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that mouse ESC, maGSC, and iPSC lines are highly susceptible targets for LAK cells as well as purified IL-2-activated NK cells ( 32 , 36 , 37 ). These pluripotent stem cell types were all killed by allogeneic and syngeneic LAK cells to a similar extent or even better than YAC-1 cells that are the typical target cell line for murine NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression patterns of these NK receptor ligands cannot explain the higher susceptibility of PSC A3 than PSC A6 cells to LAK and NK cells that we observed in our experiments. The functional relevance of the NKG2D receptor for the killing of ESCs ( 32 , 37 , 47 ) and other pluripotent stem cell types ( 36 , 37 ) has been demonstrated in inhibition and gene knockout experiments. Initially, some studies reported resistance of ESCs to NK cells ( 48 , 49 ), while we and others found them to be highly susceptible ( 32 , 36 , 47 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation